Participatory Monitoring and Evaluation on Service Delivery in Uganda: A Case of Community Development Based Services in Kabale District. - Kiraga, Bosco (Kabale University, 2023)
The purpose of the study was to examine the effect of participatory monitoring and evaluation on service delivery in Uganda: a case of community development-based services in Kabale district. The study was guided by three (3) effects of participatory planning, participatory implementation and participatory decision making by team members on service delivery in Uganda, a case of community development-based services department in Kabale District. The quantitative and qualitative data from the respondents was analysed using SPSS Version 23.0 and thematic analysis respectively. The study found out that participatory planning has a positive significant relationship with trainees’ employability r =. 0. 762** P≤.01). In addition, results showed participatory implementation positively and significantly related trainees’ employability (r =. 456, P≤.01). Lastly, there was also a significant positive relationship on participatory decision making by team members (r =.729 P≤.01). The study concludes that participatory planning, implementation and decision making of team members affects service delivery at the community development-based services department in Kabale district. The study recommends that prior to project implementation, stakeholders should be involved in project planning in order to improve service delivery for community development-based services department at Kabale district local government. This will make it simpler for the local administration of Kabale District to provide the community with high-quality services. The programmes that the community development-based service department offers to the residents of Kabale district should involve community members. Once this is accomplished, the project's beneficiaries will comprehend its requirements, ensuring its sustainability even after the donor has left. Lastly, in order for beneficiaries to embrace the project wholeheartedly and make decisions collectively in Kabale District, the report recommends that all interested parties participate in the participatory project decision-making. This should be followed by the department of community development-based services ensuring the success of all central government programmes.